The adoption of improved agricultural technologies: A meta-analysis for Africa - Arslan, Aslihan; Floress, Kristin; Lamanna, Christine; Lipper, Leslie; Asfaw, Solomon; Rosenstock, Todd S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Understanding the determinants of improved agricultural technology adoption is an important component of increasing agricultural productivity and incomes of smallholders to reduce poverty and hunger, which are the top two Sustainable Development Goals. Among the actions needed to achieve this, particular attention is paid to the identification and promotion of productivity and resilience enhancing agricultural practices. The micro-economic literature on the analysis of the drivers of agricultural technology adoption is well-established since the Green Revolution. Although numerous seminal reviews of this literature have been published, most of these were theoretical or conceptual reviews and focus on earlier literature from continents other than Africa, which is the continent facing the biggest productivity challenge now. This paper synthesizes the findings of this literature focusing on Africa using a meta-data set that brings together the results of 168 recently published papers. We find that most of this literature focuses on agronomic practices and that agroforestry and livestock related studies make up less than one fifth of the total published papers. Eleven determinants, primarily those related to information access, wealth indicators and tenure security, are found to increase adoption more than chance would dictate in the literature. Our findings provide evidence to support recommendations for future policy and research.